2021
DOI: 10.1183/13993003.01296-2021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tezepelumab on airway hyperresponsiveness to mannitol in asthma (UPSTREAM)

Abstract: Rationale and objectivesThymic stromal lymphopoietin (TSLP), an epithelial upstream cytokine, initiates production of type-2 (T2) cytokines with eosinophilia and possibly airway hyperresponsiveness (AHR) in asthma.This study aimed to determine whether tezepelumab (a human monoclonal antibody targeting TSLP) decreases AHR and airway inflammation in patients with symptomatic asthma on maintenance treatment with inhaled corticosteroids.Methods and measurementsIn this double-blind, placebo-controlled randomised tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 27 publications
5
92
0
2
Order By: Relevance
“…The first landmark trial to assess the efficacy of tezepelumab was carried out in mild asthmatics, which showed significant improvement in FEV 1 and reduction of peripheral and sputum eosinophils, along with decreased FeNO levels during the late phase response post-allergen provocation ( Gauvreau et al, 2014 ). Subsequent RCTs in severe asthmatics showed that tezepelumab treatment resulted in a 44–71% reduction in AAER, irrespective of baseline peripheral eosinophilia ( Table 6 ) ( Marone et al, 2019 ; Corren et al, 2021a ; Menzies-Gow et al, 2021 ; Sverrild et al, 2021 ). Patients were also shown to have improvements in FEV 1 and symptoms, with a coinciding reduction in peripheral eosinophils and serum IgE.…”
Section: Currently Available Biological Therapy and Suboptimal Responses In Severe Asthmamentioning
confidence: 99%
“…The first landmark trial to assess the efficacy of tezepelumab was carried out in mild asthmatics, which showed significant improvement in FEV 1 and reduction of peripheral and sputum eosinophils, along with decreased FeNO levels during the late phase response post-allergen provocation ( Gauvreau et al, 2014 ). Subsequent RCTs in severe asthmatics showed that tezepelumab treatment resulted in a 44–71% reduction in AAER, irrespective of baseline peripheral eosinophilia ( Table 6 ) ( Marone et al, 2019 ; Corren et al, 2021a ; Menzies-Gow et al, 2021 ; Sverrild et al, 2021 ). Patients were also shown to have improvements in FEV 1 and symptoms, with a coinciding reduction in peripheral eosinophils and serum IgE.…”
Section: Currently Available Biological Therapy and Suboptimal Responses In Severe Asthmamentioning
confidence: 99%
“…The UPSTREAM study was a placebo-controlled intervention study (add-on of anti-TSLP(n=20) or placebo(n=20) for 12 weeks) of predominantly moderate-to-severe asthma patients with airway hyperreactivity to mannitol (12).…”
Section: Manuscriptmentioning
confidence: 99%
“…The RECONSTRUCT study was a single-arm intervention study (1600 µg inhaled budesonide once daily for 16 weeks) of steroid-free asthma patients with airway hyperreactivity (AHR) to mannitol ( www.clinicaltrials.gov identifier number NCT03034005). The UPSTREAM study was a placebo-controlled intervention study (add-on of anti-thymic stromal lymphopoietin (n=20) or placebo (n=20) for 12 weeks) of predominantly moderate-to-severe asthma patients with AHR to mannitol [ 12 ]. The SIGNATURE study was a single-arm intervention study (add-on of 37.5 mg oral prednisolone for 2 weeks) of patients with moderate-to-severe asthma [ 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tezepelumab is also expected to be effective in airway remodeling, but at present, there are no available studies of its in vitro or in vivo effects on airway remodeling. An RCT showed that tezepelumab induced a numerical improvement in the provoking dose of mannitol causing a 15% reduction in FEV1 (PD15) compared with placebo, and at the end of the treatment period, the proportion of patients without AHR to mannitol was significantly ( p < 0.05) higher in the tezepelumab group than in the placebo group [ 93 ].…”
Section: Prospects For Severe Asthma Treatmentmentioning
confidence: 99%